Quantification of Cable Bacteria in Marine Sediments via qPCR - Geelhoed, Jeanine S.; van de Velde, Sebastiaan J.; Meysman, Filip J. R. (Frontiers in Microbiology, 2020)
Cable bacteria (Deltaproteobacteria, Desulfobulbaceae) are long filamentous sulfur-oxidizing bacteria that generate long-distance electric currents running through the bacterial filaments. This way, they couple the oxidation of sulfide in deeper sediment layers to the reduction of oxygen or nitrate near the sediment-water interface. Cable bacteria are found in a wide range of aquatic sediments, but an accurate procedure to assess their abundance is lacking. We developed a qPCR approach that quantifies cable bacteria in relation to other bacteria within the family Desulfobulbaceae. Primer sets targeting cable bacteria, Desulfobulbaceae and the total bacterial community were applied in qPCR with DNA extracted from marine sediment incubations. Amplicon sequencing of the 16S rRNA gene V4 region confirmed that cable bacteria were accurately enumerated by qPCR, and suggested novel diversity of cable bacteria. The conjoint quantification of current densities and cell densities revealed that individual filaments carry a mean current of 110 pA and have a cell specific oxygen consumption rate of 69 fmol O2 cell-1 day-1. Overall, the qPCR method enables a better quantitative assessment of cable bacteria abundance, providing new metabolic insights at filament and cell level, and improving our understanding of the microbial ecology of electrogenic sediments.